2012
DOI: 10.2172/1040714
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Report on the Removal of Pertechnetate From Tank 241-an-105 Simulant Using Purolite A530e

Abstract: This effort falls under the technetium management initiative and will provide data for those who will make decisions regarding the handling and disposition of technetium. To that end, the objective of this effort is to challenge Purolite®l A530E against a double-shell tank simulant from tank 241-AN-105 spiked with pertechnetate (Tc04} The Purolite ® A530E is commercially available and is currently being used at the 200 West Pump and Treat Groundwater Treatment Plant to remove pertechnetate. It has been demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Since it was not discussed, it is assumed that the simulant was spiked at room temperature. It was reported that including or omitting glycolate did not affect Tc adsorption results when using anion exchange resin Purolite ® A530E 54 (although this detail was omitted in Revision 1 of that document for unknown reasons). Sodium was in the range of 5.5 to 6.5 M. Duncan et al also saw high Tc decontamination using the pertechnetatespiked simulant and a reductive tin apatite adsorbent up to pH 12.…”
Section: Glycolate Bearing Waste and Evidence Of Non-pertechnetatementioning
confidence: 99%
“…Since it was not discussed, it is assumed that the simulant was spiked at room temperature. It was reported that including or omitting glycolate did not affect Tc adsorption results when using anion exchange resin Purolite ® A530E 54 (although this detail was omitted in Revision 1 of that document for unknown reasons). Sodium was in the range of 5.5 to 6.5 M. Duncan et al also saw high Tc decontamination using the pertechnetatespiked simulant and a reductive tin apatite adsorbent up to pH 12.…”
Section: Glycolate Bearing Waste and Evidence Of Non-pertechnetatementioning
confidence: 99%